**Guide :**

**Guide :**

... (y-5)=0 =>(2y+5)(y-5) =>y=-5/2,y=5 Substitute these into equation (3) x=(-5/2+1)/3=-1/2," "x=(5+1) ... SOCRATIC Subjects . Science Anatomy ...

Read More At : socratic.org...

2x + y = 1 x^2 + y^2 = 1 (This is the Unit Circle for Trig.) x^2 + (1 ... 5x^2 - 4x = 0 x(5x - 4) = 0 x = 0 or x = 4/5 y = 1 or y = 1 - 2(4/5) = -3/5 Solutions are (0 ...

Read More At : www.wyzant.com...

... (-5 + 2x)(x + 1) = 2 Reorder the terms: (-5 + 2x)(1 + x) = 2 Multiply (-5 + 2x) * (1 + x) (-5(1 + x) + 2x * (1 + x)) = 2 ((1 * -5 + x * -5) + 2x * (1 + x)) = 2 ...

Read More At : www.geteasysolution.com...

... (-1, -2.5) Given the equation of a parabola, y = ax^2 + bx + c, ... What is the vertex of #y=1/2x^2+x-2#? ... (x^2+2x+5) dx by using ...

Read More At : socratic.org...

- If you need clarification, ask it in the comment box .

- It's 100% free, no registration required.